Pengaruh Diameter Ahukle’an dan Takaran Kompos Biochar terhadap Pertumbuhan dan Hasil Tanaman Jagung (Zea mays L.) Lokal Putih di Lahan Kering - Maria Adisandri Aek (Savana Cendana, 2020)
Corn is one of the main food ingredients besides rice for people on the island of Timor. Therefore, people on this island have a different way of planting corn from people on other islands in Indonesia. One of the existing community cultivation techniques and is a local wisdom of the community is Ahukle’an, which is a corn cultivation technique developed by the community in the Besikama area, West Malaka District, Malaka Regency, East Nusa Tenggara (NTT). The study aims to determine the growth and yield of local maize varieties in the Ahukle’an system and the application of biochar in dry land carried out in May - September 2019 in the experimental gardens of the Faculty of Agriculture, University of Timor, Kota Kefamenanu District, Timor Tengah Utara Regency. This research uses Strip Plot Design in factorial consisting of 2 factors. The first factor is the diameter of the ahukle'an consisting of 2 levels namely 7.5 cm, 15 cm. The second factor is the dose of biochar compost consisting of 3 levels, namely without biochar compost, biochar compost 5 t / ha, biochar compost 10 t / ha. The results showed that there was an interaction between the biochar compost treatment and the ahuklean diameter of the soil temperature observation parameters 28 HST, 35 HST, 42 HST, 56 HST, and 63 HST; leaf number 42 HST, 49 HST, and 63 HST. The 15 cm diameter ahukle’an treatment affected the yield of dry shelled per plant (44.68 g). The dose of 5 t / ha biochar compost significantly affected the yield of dry shelled per plant (31.81 g).